Examining Solid Waste Management in Central Division Kabale Municipality. - Ainomugisha, Innocent (Kabale University, 2024)
The study evaluated solid waste management practices in Central Division, Kabale Municipality, using a cross-sectional survey approach with a sample size of 114 respondents. Data was collected and summarized in frequency distribution tables. The findings indicated that 42.3% of respondents considered waste collection services in the Central Division to be irregular and inefficient. Additionally, 28.6% identified limited availability of waste disposal facilities as a major issue, while 16.5% noted insufficient community awareness regarding proper waste disposal. However, 12.6% of respondents reported that certain waste management programs were effective in some areas. The study concluded that solid waste management remains a significant challenge impacting environmental health in Central Division, Kabale Municipality. Key issues included inadequate facilities, low community participation, and ineffective waste collection systems. To address these challenges, the study emphasized the need for enhanced waste management infrastructure and increased public awareness to ensure sustainable practices. Recommendations from the study included establishing consistent and efficient waste collection schedules to reduce waste accumulation, increasing the number of accessible waste disposal facilities, and implementing community awareness campaigns to educate residents on proper waste disposal methods. Furthermore, the study advocated for stronger collaboration between local government and private stakeholders to improve waste management efforts in Central Division, Kabale Municipality.